2016
DOI: 10.1116/1.4968201
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of atomic layer deposition on 3D large surface area structures: Required precursor exposure for pillar- versus hole-type structures

Abstract: Articles you may be interested in Electronic structure investigation of atomic layer deposition ruthenium(oxide) thin films using photoemission spectroscopy J. Appl. Phys. 118, 065306 (2015) Due to its excellent conformality, atomic layer deposition (ALD) has become a key method for coating and functionalizing three dimensional (3D) large surface area structures such as anodized alumina (AAO), silicon pillars, nanowires, and carbon nanotubes. Large surface area substrates often consist of arrays of quasi-one-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Comparing experimentally obtained thickness profiles with simulated profiles can provide the initial sticking probability s 0 of the used ALD reactant, as shown for instance by Rose and Bartha 12 and Ylilammi et al 14 Here, s 0 indicates the sticking probability toward the initial surface on which all reaction sites are still available. In several models, e.g., ballistic, 8,31-35 continuum, 14,[36][37][38] and Monte Carlo, 9,10,12,27,30,[39][40][41][42] it is observed that s 0 governs the slope of the leading front of the thickness profile. In this work, the relation between the slope of the profile front and the initial sticking probability has been quantified using the continuum model reported by Yanguas-Gil and Elam 36 to directly determine sticking probabilities from ALD thickness profiles without further modeling.…”
Section: B Simulating Ald Thickness Profiles In 1d Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing experimentally obtained thickness profiles with simulated profiles can provide the initial sticking probability s 0 of the used ALD reactant, as shown for instance by Rose and Bartha 12 and Ylilammi et al 14 Here, s 0 indicates the sticking probability toward the initial surface on which all reaction sites are still available. In several models, e.g., ballistic, 8,31-35 continuum, 14,[36][37][38] and Monte Carlo, 9,10,12,27,30,[39][40][41][42] it is observed that s 0 governs the slope of the leading front of the thickness profile. In this work, the relation between the slope of the profile front and the initial sticking probability has been quantified using the continuum model reported by Yanguas-Gil and Elam 36 to directly determine sticking probabilities from ALD thickness profiles without further modeling.…”
Section: B Simulating Ald Thickness Profiles In 1d Structuresmentioning
confidence: 99%
“…[6][7][8] Moreover, in cases where the dose has to be extended to reach conformal coating, the required extension can depend strongly on the reactivity of the dosed reactant. 9,10 The effect of dose and reactivity on conformality is qualitatively described in the literature through theoretical and experimental studies, 11 where the reactivities of the reactants are typically expressed in terms of their sticking probabilities toward the surface. Only a few studies focus on acquiring quantitative information on sticking probabilities, [12][13][14][15] while such quantitative information is essential for the understanding and modeling of different ALD processes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to microtrentches, micropillars offer some advantage as the more open space allows for easier deposition of the battery stack, as was shown in the case for vapor-phase deposition techniques such as atomic layer deposition (ALD). [31] However, one drawback compared to microtrenches is that free-standing pillar structures are more prone to breakage and collapse (especially when using liquid-phase deposition techniques). It is worth noting that the first functional 3D TFB was recently shown using a microtrench design, [32] as will be discussed further on.…”
Section: Modeling the Theoretical Capacity Of 3d Tfbsmentioning
confidence: 99%
“…3D (three-dimensional) Monte Carlo model was used by Cremers et al [92] to compare the deposition of an infinite array of holes and infinite arrays of pillars using atomic layer deposition on large 3D surface area. They observed that the required exposure to conformally coat an array of holes is determined by the height to width ratio of the individual holes and is independent of their spacing in the array.…”
Section: Monte Carlomentioning
confidence: 99%